THE EFFECT OF SAVINGS AND OPERATIONAL COSTS ON THE REST OF THE VILLAGE ECONOMIC BUSINESS SHU – SAVES (UD-SP) SIMPANG KOTA MEDAN, KELAYANG DISTRICT, INDRAGIRI HULU REGENCY - Yuda Remofa (Bajang Institute, 2022)
From the results of the study, the regression equation obtained is Y = 93,419 + 4.828X1 - 0,059X2, it can be seen that savings and operational costs have a positive influence on the remaining operating results (UED-SP) Village Economy - Savings and Loans (UED-SP) Simpang Medan City Kelayang District, Indragiri Hulu Regency. In addition, the simultaneous test (F test), has obtained F count > F table that is equal to 23,788 > 19.00. So that the two independent variables, namely savings and operational costs, have a positive and significant effect on the dependent variable, namely the residual income (UED-SP) of Village Economy - Savings and Loans (UED-SP) Simpang Medan City, Kelayang District, Indragiri Hulu Regency. While the Partial Regression Test (t test) shows that the savings variable that has a significant effect on the remaining operating income (UED-SP) of Village Economy - Savings and Loans (UED-SP) Simpang Medan City, Kelayang District, Indragiri Hulu Regency, namely t count > t table of 3,395 > 3.18245. While the operational cost variable has no significant effect on the remaining operating income (UED-SP) of Village Economics - Savings and Loans (UED-SP) Simpang Medan City, Kelayang District, Indragiri Hulu Regency, namely t count > t table of -0.646 < -3.18245. In addition, the results of the multiple correlation coefficient is 0.889 which indicates the level of relationship between all independent variables to the dependent variable in this study is in the criteria of a strong relationship. The magnitude of the influence caused by these two variables together affects the remaining operating results variable with a percentage of 79.1%. While 20.9% is influenced by other factors that are not involved in this study